Venation Patterns in Mimosa subseries Dolentes and Brevipedes (Leguminosae) and their Taxonomical Inferences - Grohar, Mariana Cecilia; Rosenfeldt, Sonia; Morales, Matias (2019)
Mimosa is a megadiverse genus of pantropical and subpantropical distribution. High morphological variability at infraspecific levels has often led to problems in the delimitation of taxa and the formation of taxonomic complexes. Here, on cleared leaflets of 20 taxa of the Dolentes- Brevipedes taxonomic complex, we describe three major venation types: acrodromous, parallelodromous, and brochidodromous. We provide a detailed description of variability among each one, leading to the establishment of two and five subtypes within the acrodromous and brochidodromous taxa, respectively. Venation architecture clearly differentiates three species within Mimosa subseries Brevipedes: M. brevipes with acrodromous, M. fernandez-casasii with parallelodromous venation, and M. diversipila by its brochidodromous weak pattern. Three varieties are alsorecognizable in brochidodromous subseries Dolentes: M. dolens var. anisitsii with round pattern, M. dolens var. eriophylla and M. dolens var. rudis with ample pattern.